PEMANFAATAN MEDIA ARTIFICIAL INTELLEGENCE DALAM MENINGKAT-KAN LITERASI TERHADAP HASIL BELAJAR IPAS MATERI DI BUMI DAN KRISIS ENERGI PADA MURID KELAS IV MI AL-BUKHORI SURABAYA - Achmad Fajar Yusro; Suprihatien; Yudha Popiyanto Suprihatien (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the low literacy rates and suboptimal learning outcomes in Natural and Social Sciences (IPAS) among 6th-grade students at MI Al-Bukhori Surabaya, where average scores remained below the school's minimum mastery criteria (KKTP) of 79 due to low engagement and underutilized digital tools for academic learning. This research aims to evaluate the effectiveness of utilizing ChatGPT-based Artificial Intelligence (AI) media to improve literacy and learning outcomes regarding "Energy on Earth and Energy Crisis." A quantitative approach with a quasi-experimental design (Non-equivalent Control Group Design) was employed. The study involved 36 students selected through non-random sampling, divided into an experimental group (Class VI-B, 16 students) using ChatGPT and a control group (Class VI-A, 20 students) utilizing conventional textbooks. Data collection relied on pretest and posttest instruments validated through expert judgment, and quantitative data were analyzed using the Independent Samples T-Test in SPSS version 29.0. The findings revealed that the experimental group achieved an exceptional posttest average score of 92.69 with a 100% mastery rate, whereas the control group only scored an average of 75.30. Hypothesis testing yielded a significance value of p = 0.001 (< 0.05), which successfully rejected the null hypothesis (H0). In conclusion, the integration of Artificial Intelligence media significantly enhances students' literacy skills and academic performance in IPAS, providing an innovative and adaptive learning alternative for elementary education in the digital era.